Is LRRK2 the missing link between inflammatory bowel disease and Parkinson’s disease? - Mary K. Herrick; Malú G. Tansey (npj Parkinson's Disease, 2021)
Abstract Links that implicate the gastrointestinal system in Parkinson’s disease (PD) pathogenesis and progression have become increasingly common. PD shares several similarities with Crohn’s disease (CD). Intestinal inflammation is common in both PD and CD and is hypothesized to contribute to PD neuropathology. Mutations in leucine-rich repeat kinase 2 (LRRK2) are one of the greatest genetic contributors to PD. Variants in LRRK2 have also been associated with increased incidence of CD. Since its discovery, LRRK2 has been studied intensely in neurons, despite multiple lines of evidence showing that LRRK2 is highly expressed in immune cells. Based on the fact that higher levels of LRRK2 are detectable in inflamed colonic tissue from CD patients and in peripheral immune cells from sporadic PD patients relative to matched controls, we posit that LRRK2 regulates inflammatory processes. Therefore, LRRK2 may sit at a crossroads whereby gut inflammation and higher LRRK2 levels in CD may be a biomarker of increased risk for sporadic PD and/or may represent a tractable therapeutic target in inflammatory diseases that increase risk for PD. Here we will focus on reviewing how PD and CD share overlapping phenotypes, particularly in terms of LRRK2 in the context of the immune system, that could be targeted in future therapies.